Implementasi Fungsi Protokoler Sekretariat Daerah Dalam Mendukung Kelancaran Agenda Pimpinan Daerah - Aloysius Alfianto Elang; Intan Mustafa; Markus Retu (JUPEIS : Jurnal Pendidikan dan Ilmu Sosial, 2026)
This study aims to analyze the implementation of protocol functions within the Regional Secretariat in supporting the smooth execution of regional leaders’ agendas from a communication studies perspective using a Public Relations approach. Protocol functions play a strategic role in managing formal communication, event arrangements, and institutional relations that directly influence the image and authority of regional leaders. This research employs a qualitative approach with a case study method. Data were collected through observation, in-depth interviews, and documentation of protocol activities and relevant stakeholders. Data analysis was conducted descriptively using George C. Edwards III’s Policy Implementation Theory, which emphasizes four key variables: communication, resources, disposition, and bureaucratic structure. The findings indicate that the protocol functions of the Regional Secretariat have been systematically implemented to support the effectiveness of leadership agendas, particularly through well-coordinated communication and structured event management. However, challenges remain in terms of resource availability and inter-unit coordination, which affect the optimization of protocol implementation. This study concludes that protocol functions extend beyond administrative duties and represent a strategic Public Relations practice that contributes to building the image, credibility, and public legitimacy of regional leaders.